Bij het afscheid van een dame. De Roermondse Sint Elisabethvereniging in 1909 - Heemels, Maurice (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
At the farewell of a lady. The Roermond women’s charity of Saint-Elisabeth by 1909In the Low Countries, poor relief was primarily the responsibility of private organisations until the early twentieth century. One out of many was the Roermond ‘Sint Elisabethvereniging’, a Roman Catholic women’s charity that tried to help the urban poor in times of unemployment, illness, old age and financial worries. By 1909 the work of the Sint Elisabethvereniging was done by fifteen women. Being part of the Roermond elite, many of these ladies were related to one another. Only four of them were married, and their husbands, like the fathers and brothers of the other ladies, were almost exclusively working as legal experts (lawyers, judges and notaries). The ladies lived near to each other in the better neighbourhoods of the city. It was almost impossible for outsiders to become a member of this rather exclusive group of ladies. Charity provided them with a means of fulfilling their Christian duties and confirming their social status. Furthermore the work gave them the opportunity to meet other women at a time when women of the higher social classes were expected to stay at home. For most of the ladies their membership of the Roermond Sint Elisabethvereniging was also ‘an escape from loneliness’.